On the Physical Vapour Deposition (PVD): Evolution of Magnetron Sputtering Processes for Industrial Applications - Baptista, Andresa (2020)
Advanced coatings play an important role in a wide range of industrial applications. These coatings are commonly used in machining tools due to their high hardness and wear resistance, but also can be applied in jewellery and decorative purposes. Deposition techniques have seen a strong evolution as result of the directly related devices, control evolution and software. Several variants have been developed around the main techniques: arc evaporation and sputtering. The coatings produced present significant differences in their characteristics, namely in terms of structure, mechanical properties and surface morphology. Depending on the substrate material and application, the deposition process needs to be properly selected, providing the particular characteristics requested. This paper intends to do a critical review of the evolution of the advanced coatings deposition process, mainly focused on the Physical Vapour Deposition (PVD) process, particularly in the Magnetron Sputtering technique, which is able to produce smooth surfaces, using lower temperatures, presenting excellent mechanical and tribological properties and having very good adhesion to the main materials used as substrate.